2014
DOI: 10.1155/2014/639856
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Red Propolis Induces Apoptosis‐Like Cell Death and Decreases Migration Potential in Bladder Cancer Cells

Abstract: Natural products continue to be an invaluable resource of anticancer drug discovery in recent years. Propolis is known for its biological activities such as antimicrobial and antitumor effects. This study assessed the effects of Brazilian red propolis (BRP) on apoptosis and migration potential in human bladder cancer cells. The effect of BRP ethanolic extract (25, 50, and 100 μg/mL) on 5637 cells was determined by MTT, LIVE/DEAD, and migration (scratch assay) assays. Apoptosis induction was investigated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 45 publications
2
37
0
1
Order By: Relevance
“…It was verified that the extracts obtained from red propolis (RSE and RAL) originated from the Brazilian northeast showed the highest content of phenolic compounds and flavonoids. This confirms the biological potential of this “new” type of propolis [ 4 , 74 76 ]. The highest quantity of total phenols, flavonoids and the best antioxidant activity by ABTS was identified in the extract of red propolis from the state of Sergipe (SER EtOH), with values of 300.36±0.01 mg EAG/g, 57.60±0.01 mg EQ/g and 98.50±1.40%, respectively ( Table 4 ).…”
Section: Resultssupporting
confidence: 72%
“…It was verified that the extracts obtained from red propolis (RSE and RAL) originated from the Brazilian northeast showed the highest content of phenolic compounds and flavonoids. This confirms the biological potential of this “new” type of propolis [ 4 , 74 76 ]. The highest quantity of total phenols, flavonoids and the best antioxidant activity by ABTS was identified in the extract of red propolis from the state of Sergipe (SER EtOH), with values of 300.36±0.01 mg EAG/g, 57.60±0.01 mg EQ/g and 98.50±1.40%, respectively ( Table 4 ).…”
Section: Resultssupporting
confidence: 72%
“…An analysis of the available anticancer drugs revealed that the majority of approved anticancer drugs are unmodified natural products or their semisynthetic derivatives, or molecules synthesized based on natural product compound pharmacophores (1). Natural products are considered a promising source for future drugs (2). It has previously been demonstrated that aloperine, oxymatrine, sophoridine and cytisine exert antitumor effects, with some having important roles in cancer treatment (3).…”
Section: Introductionmentioning
confidence: 99%
“…Baccharis dracunculifolia DC (Asteraceae) is a native plant from Brazil and it is considered the most important botanical source of green propolis, predominant in the Brazilian southeast [ 4 ]. Different studies have demonstrated the biological properties of propolis extracts such as its anti-oxidant action [ 5 6 ], antimicrobial action [ 7 – 9 ], anti-inflammatory action [ 10 11 ], anti-parasite action [ 12 13 ], immune-modulatory action [ 14 15 ], anti-tumor action [ 16 19 ], antiviral action [ 20 21 ] and others [ 22 23 ]. These biological activities are especially attributed to the phenolic acids, flavonoids, terpenes and sesquiterpenes present in the propolis [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%